Implementing Learning Design by lams to improve teaching and learning - Lengyel , Péter; Herdon, Miklós (Applied Studies in Agribusiness and Commerce, 2009)
Learning Design has the potential to revolutionize e-learning by capturing the process of education, rather than simply content. By describing sequences of collaborative learning activities, Learning Design offers a new approach to re-use in e-learning. E-learning has a well developed approach to the creation and sequencing of content-based, single learner, self-paced learning objects.While definitions of Learning Design vary, the main elements tend to include greater focus on context dimensions of e-learning, a more activity based view of e-learning, and greater recognition of the role of multi-learner environments. While Learning Design does not exclude single learner, self-paced modes of elearning, it draws attention to a wider range of collaborative e-learning approaches in addition to single learner approaches. This paper shows an example, which is applied to speciality of economic and rural development agricultural engineer at University of Debrecen and its implementation in the Learning Activity Management System. We created a learning design was implemented at this speciality with LAMS, which is a learning design editing and play back tool that puts the learning process, rather than collections of content, at the heart of e-learning.